Pengaruh Gaya Belajar dan Kedisiplinan Belajar terhadap Hasil Belajar Matematika Kelas V Sekolah Dasar - Mafaza, Zahiya Aina; Junaedi, Akhmad (Paedagogie, 2026)
This study aims to analyze the effect of learning styles and learning discipline on the mathematics learning outcomes of fifth-grade elementary school students, both partially and simultaneously. This study uses a quantitative approach with a correlational approach. The research subjects consisted of 35 fifth-grade students. Data collection techniques were carried out through questionnaires to measure learning styles and learning discipline, as well as documentation of mathematics learning outcomes. The data were analyzed using descriptive and inferential statistics with the help of the SPSS program, including prerequisite analysis and multiple linear regression tests. The results showed that learning style had a positive and significant effect on mathematics learning outcomes. Study discipline had a positive and significant effect on mathematics learning outcomes. Simultaneously, learning style and learning discipline had a significant effect on learning outcomes with a contribution of 86.5%. The conclusion of this study shows that an appropriate learning style and high learning discipline play an important role in improving elementary school students' mathematics learning outcomes.